RESOURCE ASSESSMENT FOR TARGETED STATES (Tufts Archival Research Center, 2007)
Confidential; Memorandum from Savarese and Associates to Jeff Ross assessing the labor resources available in various states to support a pro-tobacco stance. Identifies Michigan, Ohio, Massachusetts and Pennsylvania as having an optimum resource base. Targets Illinois, Oregon, Washington and Wisconsin as having a good resource base. Discusses the less-than-optimum resources in Florida, Texas, New York, New Jersey, Louisiana, Missouri, Virginia, North Carolina and Colorado. Names specific unions and personal contacts for each state listed.